Digital Learning Media Needs Analysis of Plant Physiology to Improve Learning Ownership and Creative Thinking Skills at Universitas Negeri Malang - Luffi Karimah; Balqis Balqis; Herawati Susilo (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: The digital transformation of higher education demands instructional media that not only deliver content but also foster reflective engagement and self-directed learning, particularly in experimental biology learning characterized by complex and abstract concepts. Despite the growing implementation of digital tools, limited empirical research has systematically examined learning media needs as a foundational stage prior to development, especially in relation to learning ownership and creative thinking skills in the Plant Physiology courses. Methodology: The research methods employed a descriptive mixed-method design. Participants consisted of 42 undergraduate students selected through purposive sampling and four Plant Physiology lecturers. Data were collected through questionnaires, semi-structured interviews, and analysis of lesson plans (RPS and SAP). Quantitative data were analyzed using descriptive statistics and categorical percentage classification, while qualitative data were analyzed thematically and integrated through data triangulation. Findings: The findings indicate that instructional practices remain dominated by PowerPoint presentations (58.6%) and summative assessments such as written examinations (22.8%), with minimal implementation of reflective and process-oriented assessment. Students’ learning ownership was categorized as proficient (78.4%), with persistence scoring highest (84.1%) and goal orientation and self-direction lowest (69.6%). Creative thinking skills were also categorized as proficient (76%), with collaboration highest (85.4%) and elaboration lowest (69.6%). These patterns reveal specific dimensions requiring instructional reinforcement, particularly in self-direction and idea elaboration. These findings highlight the need to develop interactive digital learning media grounded in Deep Learning and Problem-Based Learning (PBL), which can facilitate reflection, collaboration, and systematic documentation of the learning process. Media such as e-portfolios are considered relevant to strengthen learning ownership and enhance students’ creative thinking skills in the Plant Physiology course. Contributions: This study contributes by providing an empirical, needs-based foundation for the systematic design of digital learning media in experimental biology learning, thereby informing future development and effectiveness research in higher education contexts